2019
DOI: 10.1016/j.bodyim.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a model for risk and protective factors for eating disorders and higher weight among emerging adults: A study protocol

Abstract: Research has demonstrated that eating disorders and higher weight have lifetime cooccurrence suggesting that they may be best considered within a common etiological model. Although we know that body dissatisfaction is likely to be a risk factor for both disorders, other proposed risk and protective factors for each condition have not been adequately explored. The current paper tests a conceptual model that is based on a review of the existing literature from both areas of scholarship. It considers biological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 65 publications
1
12
0
2
Order By: Relevance
“…These data are consistent with the results of other studies conducted on various populations and nationalities, which indicate the increasing epidemiology of eating disorders around the world [1,19]. The results also confirm the significant role of socio-cultural predictors in the development of body dissatisfaction, which is one of the risk factors of eating disorders [2,39,70,78,85,86]. The results show that the significant predictors of variables such as Body Dissatisfaction and bulimic tendencies (Bulimia) for Japanese women were Emotional Dysregulation and Interoceptive Deficits-the former describes affective difficulties involving emotional dysregulation, such as emotional instability and impulsiveness, while the latter is related to disorientation and difficulties with identification and differentiation of emotional states and bodily sensations.…”
Section: Predictors Of Eating Disorders Among the Studied Groups Of Psupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with the results of other studies conducted on various populations and nationalities, which indicate the increasing epidemiology of eating disorders around the world [1,19]. The results also confirm the significant role of socio-cultural predictors in the development of body dissatisfaction, which is one of the risk factors of eating disorders [2,39,70,78,85,86]. The results show that the significant predictors of variables such as Body Dissatisfaction and bulimic tendencies (Bulimia) for Japanese women were Emotional Dysregulation and Interoceptive Deficits-the former describes affective difficulties involving emotional dysregulation, such as emotional instability and impulsiveness, while the latter is related to disorientation and difficulties with identification and differentiation of emotional states and bodily sensations.…”
Section: Predictors Of Eating Disorders Among the Studied Groups Of Psupporting
confidence: 91%
“…Furthermore, research must test a model with many variables-biological, physical, psychological, and socio-cultural-to identify the multifaceted influence of restrictive and bulimic behaviours on eating and the body [39]. In addition to physical (e.g., BMI-Body Mass Index) and socio-cultural risk factors, the psychological factors supporting the development of unhealthy eating behaviours are also worth mentioning.…”
Section: Risk Factors For Eating Disordersmentioning
confidence: 99%
“…In fact, in this study athletes seem to experience fewer states of tension and anxiety than the sedentary population, considered to be protective since symptomatic mood states (i.e., overestimation of shape, weight, and food control) are risk factors in EDs [44]. A recent large study conducted by McCabe et al in 2019 has confirmed that depressive as well as anxiety symptoms may be included as "psychological" risk factors in a conceptual framework of risk for eating disorders [45]. Moreover, several studies have suggested that mood depression disorder (MDD) is commonly diagnosed as comorbidity with EDs [46][47][48].…”
Section: Discussionmentioning
confidence: 56%
“…La capacidad de influencia que tienen los medios de comunicación, en general, puede advertirse ya desde los estudios realizados a nivel mundial por autores como los de McCabe y Ricciardelli (2005), o los de de Skemp-Arlt et al (2006), donde se muestra que la mitad de los niños de entre 5 y 12 años se sienten insatisfechos con su aspecto físico. Y es que, tal y como afirman McCabe et al (2019), Mancilla et al (2012), Skemp-Arlt et al (2006), McCabe & Ricciardelli (2005), Phares et al (2004), Davison et al (2003), Hendy et al (2001) o Abramovitz & Birch (2000), alrededor de un 40-50% de los niños entre 6-12 años se sienten insatisfechos con su aspecto físico. De hecho, las evidencias científicas (De Jans et al, 2019) constatan que esta insatisfacción afecta a ambos géneros, pero el tipo de distorsión difiere en función del género.…”
Section: Los Media Y La Construcción De La Imagen Corporalunclassified
“…Enfermedades relacionadas con los hábitos alimentarios, tales como la obesidad, la anorexia o la bulimia, vienen aumentando en sociedades desarrolladas o en vías de desarrollo (Haas et al, 2010). El Ministerio de Sanidad y Consumo del Gobierno de España alertaba, en 2018, de las cifras que alcanzaba la obesidad (15%) y las EDDs 2 (12%): el grupo de edad de mayor incidencia es el de los menores de entre 6 y 12 años (McCabe et al, 2019). Esta cuestión atañe a los media (Levine & Murnen, 2009;Lara & Lara, 2018), que se configuran como educomunicadores, debido a la influencia que suponen en los niños al emitir ciertos valores, susceptibles de ser asumidos por estos (Carrillo et al, 2011).…”
Section: Introductionunclassified